The impact of service separation on customer-firm relationships: A social exchange perspective - Alhathal, Faisal Thamer J. (Curtin University, 2015)
Building on a number of theoretical grounds from social and marketing domains, this thesis investigates the impact of service separation on customer-firm relationships. The thesis utilises an empirical approach using data collected from retail banking in Saudi Arabia. Findings indicate a number of interesting results pertaining to the impact of service separation. While separation may further enhance the perception of convenience, it presents potentially alarming effects on customer-firm relationship quality, loyalty and word-of-mouth.